2021
DOI: 10.3802/jgo.2021.32.e15
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of 3D-printed templates assisted CT-guided radioactive iodine-125 seed implantation for the treatment of recurrent cervical carcinoma after external beam radiotherapy

Abstract: Objective: To investigate the safety and efficacy of 3-dimensional (3D) printing noncoplanar templates (PNCT) assisted computer tomography (CT) guided radioactive 125 I seed implantation (RISI) for the treatment of recurrent cervical carcinoma (RCC) after external beam radiotherapy (EBRT). Methods: A total of 103 patients with inoperable post-EBRT RCC were included in this retrospective study. A total of 111 lesions received RISI. Eight lesions were at the pelvic center, 75 lesions were at the pelvic lateral, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 39 publications
2
29
0
Order By: Relevance
“…Accumulating evidence showed its good efficacy in various recurrent cancers, including rectal cancer, head and neck cancer, and pancreatic cancer [ 17 , 34 , 35 , 36 , 37 , 38 ]. Moreover, our previous studies demonstrated that 3D-PNCT-assisted CT-guided RISI is a safe, effective, and minimally invasive modality to treat recurrent cervical cancer after radiotherapy [ 16 , 20 ]. Other centers showed similar results [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Accumulating evidence showed its good efficacy in various recurrent cancers, including rectal cancer, head and neck cancer, and pancreatic cancer [ 17 , 34 , 35 , 36 , 37 , 38 ]. Moreover, our previous studies demonstrated that 3D-PNCT-assisted CT-guided RISI is a safe, effective, and minimally invasive modality to treat recurrent cervical cancer after radiotherapy [ 16 , 20 ]. Other centers showed similar results [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study [ 16 ], which included 111 lesions from 103 patients, the response (complete response, CR/PR/stable disease, SD) of tumors after RISI was 99.1%. The local control (LC) for one year and three years was 87.4% and 75.1%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations